Rovibronic photoionization dynamics of ammonia isotopomers - Hollenstein, U; Merkt, F; Meyer, L; Seiler, R; Softley, T; Willitsch, S (2007)
PFI-ZEKE photoelectron spectra of the [image omitted] 2B1 (v2+=3) cationic vibrational state and photoionization spectra of autoionizing Rydberg series converging on the +=1 ionization threshold of the mixed isotopomers of ammonia, NH2D and ND2H, are reported for the first time. The observed rovibronic photoionization propensities and the quantum defects of the Rydberg series indicate that the photoelectron is ejected as a superposition of even (s and d) partial-wave components in agreement with predictions from the orbital-ionization model [S. Willitsch and F. Merkt, Int. J. Mass Spectrom. 245, 14 (2005)]. The ionization energies of the v2+=3 thresholds of NH2D and ND2H were determined to be IE / hc = 84 792.9(6) cm- 1 and IE / hc = 84 595.9(8) cm- 1, respectively, and rotational constants for the [image omitted] = 3 states of both isotopomers are derived.